EXPERIENCE STUDENT BACKGROUND AND THEIR BEHAVIOR IN PROBLEM SOLVING - Yulyanti Harisman; Muchamad Subali Noto; Wahyu Hidayat (Jurnal Infinity, 2020)
These Students' mathematical problem solving behavior had been presented in the previous paper. Four categories of students' mathematical problem solving behavior in junior high schools in Indonesia had been obtained. These categories were: naive, routine, semi-sophisticated, and sophisticated. This paper was a continuation of that research. In this session would discuss about external aspects affect student behavior in problem solving. This research used survey method. Eighteen students from three junior high schools in Indonesia had been interviewed about it. These three aspects were: distance of home from school, family background, Contests-contests like math Olympiads that had been followed. The interview results were coded to get conclusions. Research findings were that the external aspects of students did not influence students in behaving to solve problems in mathematics. the implication of this finding is that the main factor influencing student behavior in problem solving is teacher professionalism in learning not from the students themselves, so the teacher must be really prepared in designing all components of learning well.